PENDEKATAN FILOSOFIS TERHADAP KEPEMIMPINAN TRANSFORMASIONAL DI LEMBAGA PENDIDIKAN - Efa Herlina Batubara; Eva Rosdiana Br Sitepu; Nurul Ismalia; Muhammad Amir Masruhim; Dwi Nugroho Hidayanto; Warman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the philosophical foundations of transformational leadership in educational institutions through the lenses of ontology, epistemology, and axiology. Using a literature review and content analysis approach, the research examines works related to leadership theory, educational philosophy, and organizational management. The findings reveal that transformational leadership is grounded in an ontological understanding of humans as agents of change who shape organizational dynamics. Epistemologically, knowledge in this leadership model is constructed through reflection, collaboration, and dialogical processes. Axiologically, values such as integrity, justice, and participatory ethics serve as the moral foundation for leadership actions. These findings affirm that transformational leadership represents a philosophical framework highly relevant to addressing 21st-century educational challenges and fostering sustainable transformation within educational culture and practice.